The military and the sustenance of democracy in Nigeria (2008)
This paper explores the role of the military In democratic development worldwide. It argues that although the military is implicated in the demise of democracy in several countries, the establishment and sustenance of major democracies owe to the achievement of a strong military force. New democracies like Nigeria faced a real challenge concerning the role of the military in governance and were at critical moments unsure of what to do. The pressures for democracy while calling for the removal of the military from governance raises the issue of how to ensure capable and stable military institutions and ensure that they remain confined to their constitutional and public policy roles. The military is a democratic necessity with a paradoxical challenge to democratic order. Hence, the paper examines how the challenge of the military to democracy is characterised and the measures adopted to deal with it worldwide. It then examines the constitutional roles and policy tasks of the Nigerian military, teases out the peculiar challenges of the military for Nigeria and provides insight for repositioning the military to proficiently execute its functions in order to sustain democracy in the country.